The level of educational excellence among teachers applying for the Queen Rania Award in Mafraq District schools - الخزاعلة شادي (Jadara Journal of Social Sciences, 2023)
Abstract The study aimed to identify the level of educational excellence among teachers who applied for the Queen Rania Award from the point of view of the principals of the Mafraq District schools, The descriptive survey method was used. The study sample consisted of (145) principals. A paragraph, and the results of the study showed the level of educational excellence among the teachers applying for the Queen Rania Award from the point of view of the principals of the Mafraq District schools, which came with a (high) degree. The effect of the variable years of experience, academic qualification, and educational qualification. Keywords: level Excellence, educational excellence, Queen Rania Al Abdullah Award, Distinguished Teacher